Socio-psychological risk factors associated with Farmers’ suicides in Vidarbha - N.M.Kale; S.R.Khonde; D.M.Mankar; E.R.Patil (Journal of Agricultural Extension Management, 2025)
A study was carried out during 2008-2009 in six suicide hit districts namely Yavatmal, Washim, Buldana, Akola, Amravati and Wardha of Vidarbha region of Maharashtra using exploratory research design. Respondents were the households of selected victims. A total of 200 victims were selected by proportionate method of random sampling. The sample covers 178 villages and 34 tehsils I talukas of six districts. The main objective of this study was to know the different socio-psychological risk factors associated with an individual victim externally within the last five years of suicide incidence. The study revealed that there were three common risk factors which coexisted with over two third of the deceased farmers , and these were increased indebtedness (94.00%), drop in economic status (84.50%) and hopelessness due to crop failure (78.50%) and these factors show the deteriorated economic condition of the deceased farmers. With 71 .50 per cent of the victims, 5 to JO risk/actors were associated. The path analysis reveals that the annual income contributed significantly in identified number of risk factors of suicide in terms of maximum negative direct effect and maximum negative indirect effect through other variables while socio-economic status indicated maximum negative total indirect effect on identified risk factors of suicides